Desain Modul Ajar Berbasis Integrasi Bahasa Arab Dan Inggris Di Lembaga Bahasa STAI Pati Jawa Tengah - Rufa Hindun Farhisiyati; Ahmad Rois; Ashief El Qorny (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2024)
This research aims to create a learning module design that will be applied to Arabic and English language learning at the STAI Pati Language Institute. Due to development research, the RnD method is used. The implementation is to design a module that is validated by experts and then tested on a limited scale. After revision, it will then be implemented on a wide scale. The results of this research produce products that can be used for dual language learning and can improve students' abilities in learning activities at the STAI Pati language institute.